Performance analysis of a biomass gasification-based CCHP system integrated with variable-effect LiBr-H2O absorption cooling and desiccant dehumidification. (1st June 2019) - Li, Xian; Kan, Xiang; Sun, Xiangyu; Zhao, Yao; Ge, Tianshu; Dai, Yanjun; Wang, Chi-Hwa
Abstract: A novel biomass gasification-based combined cooling, heat and power (CCHP) system, which is composed of a gas-fueled internal combustion engine, variable-effect LiBr-H2 O absorption cooling, and dehumidification air-conditioning with desiccant coated heat exchangers, was introduced. The temperature and humidity independent strategy was applied in the gasification-based CCHP system to enhance cooling production, in which the variable-effect absorption chiller and desiccant dehumidification air-conditioning were driven by the exhaust heat and jacket heat of the gas engine based on energy cascade, respectively. The operation strategy of the system followed the electric load. Validated by experimental data, a zero-dimensional code of the gasifier with Gibbs free energy minimization, an artificial neural network model of the variable-effect absorption chiller, and a 1-D dynamic model of the dehumidification air-conditioning, were built with reasonable deviations. The results of energetic, economic, and environmental (3E) analyses for the proposed gasification-based CCHP systems that were applied in two different buildings indicate that woody chips are the most favorable feedstock under the climate of Singapore. The total performance is more sensitive to the feedstock cost than to the natural gas cost. This work enables to contribute valuable data to the practical application of the biomass gasification-based CCHP system in Singapore's building sector. Highlights: The variable-effect absorption cooling and desiccant dehumidification were studied. 3E benefits from redwood, woody chips, and sewage sludge schemes were investigated. Total performance is more sensitive to feedstock cost than to natural gas cost. Compared to redwood and sludge, woody chips is the most favorable in Singapore.